Autoimmune Hemolytic Anemia in the Pediatric Setting - Voulgaridou, Aikaterini (J Clin Med, 2021)
Autoimmune hemolytic anemia (AIHA) is a rare disease in children, presenting with variable severity. Most commonly, warm-reactive IgG antibodies bind erythrocytes at 37 °C and induce opsonization and phagocytosis mainly by the splenic macrophages, causing warm AIHA (w-AIHA). Post-infectious cold-reactive antibodies can also lead to hemolysis following the patient’s exposure to cold temperatures, causing cold agglutinin syndrome (CAS) due to IgM autoantibodies, or paroxysmal cold hemoglobinuria (PCH) due to atypical IgG autoantibodies which bind their target RBC antigen and fix complement at 4 °C. Cold-reactive antibodies mainly induce intravascular hemolysis after complement activation. Direct antiglobulin test (DAT) is the gold standard for AIHA diagnosis; however, DAT negative results are seen in up to 11% of warm AIHA, highlighting the need to pursue further evaluation in cases with a phenotype compatible with immune-mediated hemolytic anemia despite negative DAT. Prompt supportive care, initiation of treatment with steroids for w-AIHA, and transfusion if necessary for symptomatic or fast-evolving anemia is crucial for a positive outcome. w-AIHA in children is often secondary to underlying immune dysregulation syndromes and thus, screening for such disorders is recommended at presentation, before initiating treatment with immunosuppressants, to determine prognosis and optimize long-term management potentially with novel targeted medications.